Analysis of The Role of Behavioral Accounting in Financial Decision Making: A Literature Study - Ricardo Parulian Sibagariang (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2026)
This study examines the role of behavioral accounting in financial decision-making through a literature review of findings from 2019–2024. It focuses on how cognitive biases, heuristics, and socio-emotional pressures affect the quality and effectiveness of financial decisions across sectors ranging from MSMEs to large corporations. The research method is a systematic narrative literature review that identifies and analyzes reliable sources from databases such as SINTA, Scopus, and Google Scholar. The synthesis shows that cognitive biases—such as overconfidence and anchoring—and heuristic strategies often distort risk and opportunity assessments, while socio-emotional pressures such as herd mentality also influence investment decisions. This study addresses fragmented literature by presenting a more holistic and applicable theoretical framework, contributing to accounting theory and practice, as well as financial policy. Although the literature review approach has limitations, including potential publication bias and methodological variation across studies, these findings are expected to support further empirical research to optimize financial decision-making in the era of digital transformation.